Seedling Growth Pattern of Guava (Psidium guajava L.) as Influenced by Different Seed Scarification Treatments - Sourabh; Sharma, Jeet Ram; Baloda, Satpal; Beniwal, Vivek (International Journal of Economic Plants, 2018)
Plant growth studies involve seed germination studies and this depends on seed viability and dormancy aspects, besides essential requirements and factors for the same. Of the various factors involved in seed germination, dormancy plays a significant role. In guava, seed dormancy is more of physical nature (due to hard seed coat) than being physiological. An experiment was conducted from March-November, 2015 at the experimental orchard of the Department of Horticulture, CCSHAU, Hisar to study effect of different scarification treatments on guava seed germination and their effect on subsequent seedling growth.Three scarification methods were used i.e. water soaking (for 24, 48 and 72 hrs), hot water soaking (at 70, 80, 90 and 100 °C) and sulphuric acid soaking (at 10, 20, 30, 40 and 50% dilution). Duration for hot water soaking and sulphuric acid soaking was kept as quick dip (5 seconds), 1 minute and 3 minutes. All these treatments significantly decreased days to emergence of seedling over control. Among the various scarification methods and durations used, treatment of guava seeds with 20%sulphuric acid for 3 minutes was judged best with maximum germination per cent (51.7%), Quick dip of guava seeds in 30%sulphuric acid resulted in better seedling growth with a maximum seedling height (42 cm) while maximum fresh weight of shoot (22.6 g ) and maximum dry weight of shoot (8.81 g) was recorded in seedlings which were subjected to scarification treatment with quick dip at 90 °C.